2013
DOI: 10.1021/bc4002757
|View full text |Cite
|
Sign up to set email alerts
|

Differential Endosomal Pathways for Radically Modified Peptide Vectors

Abstract: In the current work we characterize the uptake mechanism of two NickFect family members, NF51 and NF1, related to the biological activity of transfected plasmid DNA (pDNA). Both vectors condense pDNA into small negatively charged nanoparticles that transfect HeLa cells with equally high efficacy and the delivery is mediated by SCARA3 and SCARA5 receptors. NF1 condenses DNA into less homogeneous and less stable nanoparticles than NF51. NF51/pDNA nanoparticles enter the cells via macropinocytosis, while NF1/pDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 48 publications
0
59
0
Order By: Relevance
“…This class of innate immune receptors is known to bind negatively charged particulate ligands [110]. Other scavenger-related receptors, such as lipoprotein receptor-related protein (LRP), have been previously shown to be involved in the uptake of Tat peptide [111], and recently several studies have demonstrated the involvement of different classes of scavenger or scavenger-related receptors such as SCARAs, scavenger receptor cysteine-rich type I (M160) and SR-BI in the uptake of CPPs with different cargos including NicFects, CADY and even with cationic polymers such as PEI [112][113][114][115].…”
Section: Uptake Pathways Of Cpp and Nucleic Acid Conjugates And Nanopmentioning
confidence: 99%
“…This class of innate immune receptors is known to bind negatively charged particulate ligands [110]. Other scavenger-related receptors, such as lipoprotein receptor-related protein (LRP), have been previously shown to be involved in the uptake of Tat peptide [111], and recently several studies have demonstrated the involvement of different classes of scavenger or scavenger-related receptors such as SCARAs, scavenger receptor cysteine-rich type I (M160) and SR-BI in the uptake of CPPs with different cargos including NicFects, CADY and even with cationic polymers such as PEI [112][113][114][115].…”
Section: Uptake Pathways Of Cpp and Nucleic Acid Conjugates And Nanopmentioning
confidence: 99%
“…al. showed for the first time that a cell surface receptor was responsible for the uptake of a CPP, the stearylated TP10 analog PepFect14 (PF14), in complex with splice correcting oligonucleotides (SCO) [12]. Later, structurally related peptides PepFect15 and NickFects in complex with oligonucleotides (ONs) (SCO and plasmid respectively) were also shown to be taken up by the same receptors, namely class A scavenger receptors (SCARA) [13,14]. These findings came from the observation that the ζ-potential of PF14:SCO complexes is not positive but negative in transfection-relevant media, making direct membrane interaction or engagement of negatively charged proteoglycans unlikely to be the initial contact due to charge repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the involvement of scavenger receptor class A (SCARA) in the uptake of noncovalent CPP:ON complexes was shown for the first time (42). It was previously shown that SCARA receptors bind and mediate cellular uptake of a negatively charged molecules (43), and the involvement of SCARA was shown for the CPP PepFect14 and splice-correcting oligonucleotides (SCOs), which have negative ζ potential and NF51/pDNA (44). The nature and secondary structure of the CPP, the ability to interact with cell surface and membrane lipid components, the nature, type, and active concentration of the cargo, the cell type, and the membrane composition are the parameters that play a secondary role in the cellular uptake pathway ( Figure 1C).…”
Section: Mechanisms Of Uptakementioning
confidence: 99%